Pengaruh Penambahan Serbuk Galam Sebagai Pengganti Agregat Halus Pada Campuran Beton Mutu Normal - Anggarini, Elia Anggarini; Dyah Pradhitya Hardiani; M. Rizky Maulana Teguh (AGREGAT, 2024)
The utilization of waste from wood cuttings is uncommon, and one of the wastes that is rarely employed is the leftovers of galam wood or galam powder cuttings. On this basis, a study entitled "The Effect of Adding Galam Powder as a Substitute for Fine Aggregate in Normal Quality Concrete Mixtures" was carried out. In this study, the experimental approach was used as the research method. The percentage of galam powder waste in fine aggregate, which can range from 0% to 30%, is the independent variable in this study. Other aggregates, such as cement, fine aggregate, coarse aggregate, and water, are the study's dependent variables. The compressive strength of 28-day-old material in the normal combination has a compressive strength of 22.23 MPa, the V10 mixture has a compressive strength of 4.58 MPa, the V20 mixture has a compressive strength of 3.11 MPa, and the V30 mixture has a compressive strength of 1.41 MPa. Based on the findings, it can be concluded that using waste galam powder as a fine aggregate alternative has not been successful since the galam powder does not bind completely to the concrete